Kajian Implementasi Informasi “Pilihan Lebih Sehat” Label Kemasan Mi Instan di Indonesia - Laksono Wibowo; Nuri Andarwulan; Dias Indrasti (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2024)
The habitual and excessive consumption of instant noodles can have adverse effects on health, primarily due to their high salt content. Patterns of excessive salt intake in food consumption are a contributing factor to the prevalence of non-communicable diseases. The Indonesian government has issued labeling regulations regarding the inclusion of information on sugar, salt, fat content and health messages to educate the public in monitoring their daily salt intake independently. This study aims to identify the information provided on instant noodle packaging. The research comprises of inventory and identification of instant noodle packaging labels, as well as the processing of data from these labels. According to the nutrition fact, instant noodle soup has an average salt (sodium) content of 1627.65 mg/100 g and contributes to 109% of the recommended daily salt intake. Salt content in instant noodle soup is higher than in fried instant noodles. Regular instant noodle products with the code ML more frequently include warning about high sugar and salt content. The “healthier choice” instant noodles product has an average sodium level of 697.84 mg/100 g and contributes 47% of the recommended daily salt intake. The total fat, sugar and salt content of the “healthier choice” noodles are 50.63, 13.78, and 36.56% respectively lower than regular fried instant noodles. Awareness of consuming instant noodles with low fat, sugar and salt content is expected to reduce the risk of non-communicable diseases.